SOLUSI PEMBELAJARAN 4.0: HYBRID LEARNING - Verawati, Verawati; Desprayoga, Desprayoga (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This paper helps provide information to educators on how to apply learning that fits their style and preferences according to the learning needs of students. Students have knowledge about how to provide practical and realistic opportunities, one of which is by combining some of the best aspects of conventional learning (face to face) and information and communication technology-based learning that is done online. Face-to-face classes can be used to involve students in interactive experiences, whereas online classes promise multimedia content that is rich in knowledge at anytime and anywhere as long as internet access is available. Combining these two forms of learning is called Hybrid Learning.